Understanding the relationship between teachers' use of online demonstration videos and fidelity of implementation in MyTeachingPartner-Math/Science. (October 2017) - Barton, Emily A.; Whittaker, Jessica V.; Kinzie, Mable B.; DeCoster, Jamie; Furnari, Emily
Highlights: Positive relationship between demonstration video viewing and curricular fidelity. Potential benefit of demonstration videos not maximized due to varied and low use. Most teachers chose demonstration videos to watch based on self-identified need. Teachers identified video characteristics as useful for fidelity of implementation.